Double beta decay of 150Nd to the first excited 0+ level of 150Sm: Preliminary results - A. S. Barabash; P. Belli; R. Bernabei; R. S. Boiko; F. Cappella; V. Caracciolo; R. Cerulli; F. A. Danevich; A. Di Marco; A. Incicchitti; D. V. Kasperovych; R. V. Kobychev; et al. (Ядерна фізика та енергетика)
The double beta decay of 150Nd to the first excited 0+ level of 150Sm (Eexc = 740.5 keV) was investigated with the help of the ultra-low-background setup consisting of four HP Ge (high-purity germanium) detectors (≃225 cm3 volume each one) at the Gran Sasso underground laboratory of INFN (Italy). A highly purified 2.381-kg sample of neodymium oxide (Nd2O3) was used as a source of γ quanta expected in the decays. Gamma quanta with energies 334.0 keV and 406.5 keV emitted after deexcitation of the 01+ 740.5 keV excited level of 150Sm are observed in the coincidence spectra accumulated over 16375 h. The half-life relatively to the two neutrino double beta decay 150Nd → 150Sm(01+) is measured as T1/2 = [4.7+4.1-1.9(stat)±0.5(syst)]×1019 y, in agreement with results of previous experiments.